Policy and Implementation of Supervision in Efforts to Improve the Quality of Education - Sanuri Sanuri (International Journal of Nusantara Islam, 2026)
The quality of Indonesian education remains low in Asia, ranking below Vietnam and 12th out of 12 surveyed countries, while placing 37th out of 57 globally in competitiveness. To address this, strategic efforts through educational supervision are crucial. This descriptive qualitative study, conducted at the Office of the Ministry of Religious Affairs of Indramayu Regency, aims to analyze academic supervision, managerial supervision, supporting and inhibiting factors, and quality improvement policies for Madrasah Ibtidaiyah supervisors using interviews, observations, documentation, and triangulation. The results indicate that academic supervision is executed through planning, implementation, and reporting stages, while managerial supervision encompasses managing the curriculum, teaching staff, student affairs, personnel, facilities, public relations, and finance. Supporting factors include the proactive roles of teachers, principals, and supervisors, whereas inhibiting factors involve limited supervisor numbers, resistance to paradigm shifts, inadequate facilities, low teacher competency, weak coordination, and suboptimal regulation dissemination. Furthermore, policies to enhance supervisor quality are implemented by strengthening professionalism, career development, and education quality. To overcome existing constraints, this study recommends the implementation of innovative learning, strengthening technological facilities, improving teacher qualifications, and optimizing budgets and scholarships in a targeted manner.